Dissolved and gaseous nitrogen losses in forests controlled by soil nutrient stoichiometry - Filip Oulehle; Christine L Goodale; Christopher D Evans; Tomáš Chuman; Jakub Hruška; Pavel Krám; Tomáš Navrátil; Miroslav Tesař; Alexandr Ač; Otmar Urban; Karolina Tahovská (Environmental Research Letters, 2021)
Global chronic nitrogen (N) deposition to forests can alleviate ecosystem N limitation, with potentially wide ranging consequences for biodiversity, carbon sequestration, soil and surface water quality, and greenhouse gas emissions. However, the ability to predict these consequences requires improved quantification of hard-to-measure N fluxes, particularly N gas loss and soil N retention. Here we combine a unique set of long-term catchment N budgets in the central Europe with ecosystem ^15 N data to reveal fundamental controls over dissolved and gaseous N fluxes in temperate forests. Stream leaching losses of dissolved N corresponded with nutrient stoichiometry of the forest floor, with stream N losses increasing as ecosystems progress towards phosphorus limitation, while soil N storage increased with oxalate extractable iron and aluminium content. Our estimates of soil gaseous losses based on ^15 N stocks averaged 2.5 ± 2.2 kg N ha ^−1 yr ^−1 and comprised 20% ± 14% of total N deposition. Gaseous N losses increased with forest floor N:P ratio and with dissolved N losses. Our relationship between gaseous and dissolved N losses was also able to explain previous ^15 N-based N loss rates measured in tropical and subtropical catchments, suggesting a generalisable response driven by nitrate (NO _3 ^− ) abundance and in which the relative importance of dissolved N over gaseous N losses tended to increase with increasing NO _3 ^− export. Applying this relationship globally, we extrapolated current gaseous N loss flux from forests to be 8.9 Tg N yr ^−1 , which represent 39% of current N deposition to forests worldwide.